How do people seeking asylum in the United Kingdom conceptualize and cope with the asylum journey?. Issue 4 (1st October 2020) - Hoare, Thomas; Vidgen, Andrew; Roberts, Neil P
ABSTRACT: People seeking asylum experience traumatic events and psychological difficulties in country-of-origin, in 'flight', and during re-settlement. Research with this population has focussed on using quantitative methods to examine psychopathology from exposure to traumatic events, and there is a paucity of qualitative research exploring subjective experiences of this population throughout their asylum journey. Few studies have examined ways asylum seekers might cope with such events. This study aimed to address this gap by employing Constructivist Grounded Theory to understand the ways people seeking asylum conceptualize and cope with their experiences across the asylum process. Semi-structured interviews were conducted with eleven people seeking asylum accessing a third sector mental health project and/or primary-care health service. Four main themes emerged from the data: 'Before Asylum ', ' Displacement ', ' Identity in the UK ' and ' Reflections on the Future'. The stress of the asylum system and adaptation to new environments are core aspects of the theory, along with an exploration of how people cope with these circumstances, via internal psychological strategies and external support sources. Prior experiences (including the development of ' inner strength ') impacted upon how participants conceptualized their everyday experiences, and this shaped their considerations for the future. Service implications are discussed.